Tapeworms (Cestoda: Proteocephalidea) of firewood catfish Sorubimichthys planiceps (Siluriformes: Pimelodidae) from the Amazon River - de Chambrier, Alain; Scholz, Tomás (Folia parasitologica, 2008)
A survey of proteocephalidean cestodes found in the firewood catfish Sorubimichthys planiceps (Spix et Agassiz) from the Amazon River is provided. The following taxa parasitic in S. planiceps are redescribed on the basis of their type specimens and material collected recently in the Amazon River, near the type localities in Brazil, and in Iquitos, Peru: Monticellia lenha Woodland, 1933; Nomimoscolex lenha (Woodland, 1933) (syn. Proteocephalus lenha Woodland, 1933); and Monticellia megacephala Woodland, 1934, for which a new genus, Lenhataenia, is proposed, with L. megacephala (Woodland, 1934) comb. n. as its type and only species. The new genus is a member of the Monticelliinae, i.e. has all genital organs in the cortex, and is most similar to Chambriella in possessing biloculate suckers and lacking a metascolex. It differs in the morphology of the cirrus-sac that contains a strongly coiled, thick-walled internal sperm duct (vas deferens) and a muscular cirrus of the appearance typical of most proteocephalideans, whereas that of Chambriella is sigmoid, with voluminous, tightly sinuous thick-walled internal sperm duct. In addition, Lenhataenia possesses a well developed internal musculature, whereas the internal musculature of Chambriella is weakly developed, formed by a low number of muscle fibres. The scolex morphology and distribution of microtriches of Peltidocotyle lenha (Woodland, 1933) (syn. Othinoscolex lenha Woodland, 1933 and Othinoscolex myzofer Woodland, 1933), Chambriella sp. and Choanoscolex sp. are described using scanning electron microscopy. The two latter taxa may be new for science and are reported from S. planiceps for the first time.
Keywords: Brazil; anatomické struktury zvířat; Animals; Rivers; Peru; mikroskopie elektronová rastrovací; Catfishes; Brazílie; Microscopy; Microscopy, Electron, Scanning; Animal Structures; Cestoda; řeky; sumci; mikroskopie; zvířata